2013
DOI: 10.1093/gbe/evt159
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Diversity of the Enteric Pathogen Salmonella enterica subsp. enterica Inferred from Genome-Wide Reference-Free SNP Characters

Abstract: The enteric pathogen Salmonella enterica is one of the leading causes of foodborne illness in the world. The species is extremely diverse, containing more than 2,500 named serovars that are designated for their unique antigen characters and pathogenicity profiles—some are known to be virulent pathogens, while others are not. Questions regarding the evolution of pathogenicity, significance of antigen characters, diversity of clustered regularly interspaced short palindromic repeat (CRISPR) loci, among others, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
124
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(148 citation statements)
references
References 46 publications
21
124
2
1
Order By: Relevance
“…Given the dynamic nature of CRISPR loci with respect to spacer acquisition, loss, and duplication, we hypothesized that the identification of major S. enterica serotype Enteritidis lineages by CRISPR-MVLST was due to the imprinting of exogenous genetic cues on the CRISPRs that reflect the different ecological origins of major lineages. However, a recent study that included various Salmonella serotypes suggested that such signals might not be phylogenetically informative at the species level due to factors such as horizontal gene transfer and acquisition of common CRISPRs by different lineages (35). Further studies are necessary to investigate the robustness and scope of CRISPR subtyping in detecting ecological and evolutionary patterns of Salmonella and other organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Given the dynamic nature of CRISPR loci with respect to spacer acquisition, loss, and duplication, we hypothesized that the identification of major S. enterica serotype Enteritidis lineages by CRISPR-MVLST was due to the imprinting of exogenous genetic cues on the CRISPRs that reflect the different ecological origins of major lineages. However, a recent study that included various Salmonella serotypes suggested that such signals might not be phylogenetically informative at the species level due to factors such as horizontal gene transfer and acquisition of common CRISPRs by different lineages (35). Further studies are necessary to investigate the robustness and scope of CRISPR subtyping in detecting ecological and evolutionary patterns of Salmonella and other organisms.…”
Section: Discussionmentioning
confidence: 99%
“…All three proteins are virulence determinants in Salmonella (43)(44)(45)(46). WGS has already proved its usefulness for elucidating the evolutionary diversity of large populations of bacterial isolates (11,47,48). In the specific case of Salmonella, WGS was successfully applied to illuminate the diversity of the pathogen within a vast epidemic episode, allowing highly efficient traceback of clinical and food isolates (4,13).…”
Section: Discussionmentioning
confidence: 99%
“…Large studies based on WGS within S. enterica subspecies (10) and within serovars in S. enterica subsp. enterica (11,12) contributed to the elucidation of Salmonella phylogenetic diversity and also accomplished important steps forward in the area of bacterial disease tracking. Moreover, serovar-specific studies on S. enterica subsp.…”
mentioning
confidence: 99%
“…There are several advantages to using kSNP, which is a reference-free method of identifying genome-wide SNPs. First, the kSNP approach to gathering reference-free SNPs for downstream phylogenetic analysis has been shown to be effective for microbial-scale phylogenomic analysis (26,27). Second, it is not sensitive to assembly error because the putative SNPs are extracted from k-mers (one SNP per 25-mer in our analysis), which effectively eliminates any influence of assembly.…”
Section: Methodsmentioning
confidence: 99%